Mystics, Mavericks, and Merrymakers : an Intimate Journey among Hasidic Girls. - Levine, Stephanie Wellen (NYU Press, 2003)
From the ardently religious young woman who longs for the life of a male scholar to the young rebel who visits a strip club, smokes pot, and agonizes over her loss of faith to the proud Lubavitcher with a desire for a high-powered career, Stephanie Wellen Levine provides a rare glimpse into the inner worlds and daily lives of these Hasidic girls. Lubavitcher Hasidim are famous for their efforts to inspire secular Jews to become more observant and for their messianic fervor. Strict followers of Orthodox Judaism, they maintain sharp gender-role distinctions. Levine spent a year living in the Lub.